1983
DOI: 10.1073/pnas.80.22.7010
|View full text |Cite
|
Sign up to set email alerts
|

Carbon starvation and growth rate-dependent regulation of the Escherichia coli ribosomal RNA promoters: differential control of dual promoters.

Abstract: We studied the effects of carbon starvation and of varying the growth rate on the activity of each of the two tandem ribosomal RNA promoters from the rrnA operon of Escherichia coli. The cellular abundance of plasmid-encoded transcripts arising at promoters P1 and P2 and terminating at the ribosomal RNA terminator in promoter-terminator fusions, together with transcript turnover rates, was used to estimate promoter activities. The rate of synthesis of the P1-promoted transcript was found to increase exponentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…Within this class there are different responses to variation of growth rate. Thus the rate of expression of the rrnA P1 promoter is approximately proportional to the square of the growth rate (19) while those of the leuV and tyrT promoters are directly proportional (20,21). By contrast expression of the rpsE and rpsMR promoters is independent of growth rate, variation in the levels of the cognate mRNA species being achieved possibly by post transcriptional controls (22).…”
Section: Consensus -A T T T T T C T -mentioning
confidence: 96%
“…Within this class there are different responses to variation of growth rate. Thus the rate of expression of the rrnA P1 promoter is approximately proportional to the square of the growth rate (19) while those of the leuV and tyrT promoters are directly proportional (20,21). By contrast expression of the rpsE and rpsMR promoters is independent of growth rate, variation in the levels of the cognate mRNA species being achieved possibly by post transcriptional controls (22).…”
Section: Consensus -A T T T T T C T -mentioning
confidence: 96%
“…E. coli rRNA synthesis is regulated by the collective response of the dual promoters to growth rate (Gourse et al, 1996), amino acid starvation (Cashel et al, 1996;Gafny et al, 1994) and rRNA gene dose (Gourse et al, 1996). P1 is considered the stronger of the two promoters since it accounts for most of rRNA transcription at all but the slowest growth rates (Sarmientos & Cashel, 1983). It has been suggested that P2 promoters are inhibited by transcription from P1 (Gafny et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the signal made in response to the cell's translational capacity varies with the nutritional state of the culture. The identity of the signal is not known, although guanosine tetraphosphate (ppGpp) has been implicated as playing some role because of the virtually perfect inverse correlation between stable RNA synthesis and ppGpp concentration (36).The target of the signal, whatever its identity, has been shown in at least three of the seven rRNA operons to be P1, the more upstream of the two rRNA promoters (rrnB and rrnE [15]; rrnA [37] there is a region called the upstream activation sequence (UAS), which is required for maximal promoter activity (4,15,23).Mutations have been targeted to specific sites in the promoters rrnB P1 and tyrT, and activities resulting from the fusion of the mutant promoters to "reporter" genes have been measured under different growth conditions (15,46). Such experiments have implicated DNA sequences required for growth rate-dependent control in the region between -20 and -50 (15) and in the region just downstream of the -10 hexamer (46).…”
mentioning
confidence: 99%
“…The target of the signal, whatever its identity, has been shown in at least three of the seven rRNA operons to be P1, the more upstream of the two rRNA promoters (rrnB and rrnE [15]; rrnA [37]). The DNA sequence determinants responsible for growth rate regulation are limited to positions between -4 and -50 with respect to the transcription start site (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation